Graphene-Assisted Chemical Stabilization of Liquid Metal Nano Droplets for Liquid Metal Based Energy Storage - Sanati, Afsaneh L.; Nikitin, Timur; FAUSTO, RUI; Majidi, Carmel; Tavakoli, Mahmoud (Wiley, 2024)
Energy storage devices with liquid-metal electrodes have attracted interest in recent years due to their potential for mechanical resilience, self-healing, dendrite-free operation, and fast reaction kinetics. Gallium alloys like Eutectic Gallium Indium (EGaIn) are appealing due to their low melting point and high theoretical specific capacity. However, EGaIn electrodes are unstable in highly alkaline electrolytes due to Gallium oxide dissolution. In this letter, this bottleneck is addressed by introducing chemically stable films in which nanoscale droplets of EGaIn are coated with trace amounts of graphene oxide (GO). It is demonstrated that a GO to EGaIn weight ratio as low as 0.01 provides enough protection for a thin film formed by GO@EGaIn nanocomposite against significantly acidic or alkaline environments (pH 1-14). It is shown that GO coating significantly enhances the surface stability in such environments, thus improving the energy storage capacity by over 10x. Microstructural analysis confirms GO@EGaIn composite stability and enhanced electrochemical performance. Utilizing this, a thin-film supercapacitor is fabricated. Results indicate that when coating the EGaIn with GO to EGaIn ratio of 0.001, the areal capacitance improves by 10 times, reaching 20.02 mF cm(-2). This breakthrough paves the way for advanced liquid metal-based thin-film electrodes, promising significant improvements in energy storage applications.
Keywords: Eutectic Gallium Indium; Liquid Metal; Reduced Graphene Oxide; Stretchable Energy Storage; Supercapacitor; Wearable Electronics